Design of Dual-channel IGBT Driver Power Based on Voltage Negative Feedback Control - FAN Wei; CAO Chao; ZHONG Qiang; XU Hao (Kongzhi Yu Xinxi Jishu)
A dual-channel IGBT drive power based on voltage negative feedback control is presented. This power circuit provides dualchannel output, 15 V and -10 V, which are used to turn on and turn off the IGBT. The 15 V voltage is regulated to maintain stable regardless of the output power level, and the turn-off voltage is regulated to -6 V, while the input power is less than -21V. Finally, Pspice simulation software is used to verify its feasibility and correctness.